Empirical Analysis of Fraud Determinants in Islamic Banks: Evidence from Indonesia - Aditya, Mochammad Wisam; Dian Filianti (Jurnal Ekonomi Syariah Teori dan Terapan, 2024)
This research aims to examine the impact of sharia compliance, sharia corporate governance, and problematic financing on fraud in Sharia Commercial Banks in Indonesia from 2018 to 2023. This research uses quantitative methods with panel data regression analysis techniques to test hypotheses. The data used comes from the annual reports of Sharia Commercial Banks in Indonesia during that period. The research results show that sharia compliance, especially as measured by the Profit Sharing Ratio, and sharia corporate governance have a partial effect on fraud in Sharia Commercial Banks in Indonesia. In addition, simultaneously, sharia compliance (measured by profit sharing ratio, sharia income ratio), sharia corporate governance, and problematic financing have a significant influence on fraud in Sharia Commercial Banks in Indonesia.